Prevalence and Determinants of Food Insecurity and Association with Malnutrition of under Five Children in Aligarh - Abedi, Ali Jafar; Moin, Arshiya; Ahmad, Sameena; Mehnaz, Saira; Amir, Ali (Indian Journal of Community Health, 2021)
Background: Food security has always been a major determinant behind development of malnutrition among the under 5 children of India. Even after sustained efforts to alleviate this problem, we are still way behind in achieving our targets. Aims and Objectives: To assess the prevalence and determinants of food security, and find association of food security with stunting and wasting of children less than five years of age. Materials and Methods: This study among under five children was conducted in field practice areas of Department of Community Medicine, Jawaharlal Nehru Medical College, Aligarh Muslim University, Aligarh. Food security was assessed through Household Food Insecurity Access Scale (HFIAS) while stunting and wasting were assessed by parameters defined by World Health Organization. Statistical Analysis: Done using IBM SPSS 20.0 version. Results: 41.1% children were found to have low food security and among these 1.8% children have very low food security. Overall, statistically significant association was found between food security and malnutrition among the children (p<0.05). Significant association was also found between place of residence, caste, type of family, father’s education, father’s occupation and mother’s education. Conclusion: New health policies should be introduced, and already existing programs need to reinforce to curb this menace.